The utilization of proteins for wool growth and their effect on some physical and chemical properties - Schoeman, Emanuel Andreas (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.(Agric.)) -- University of Stellenbosch, 1969.